FUNGSI LAGU PERJUANGAN SEBAGAI PENDIDIKAN KARAKTER BANGSA - Wisnu Mintargo, RM. Soedarsono, dan Victor Ganap (Universitas Gadjah Mada, 2014)
Patriotic songs basically originated from the history of education in Indonesia, starting from intellectualcircle and teachers in pre-independence era initiated by the Boedi Oetomo movement (1908), the 1928Youth Pledge and post 1945 independence. The form and meaning of the patriotic songs, either onvocals or with instruments, take place in ceremonial activities and performance art. According to AlanM. Meriam and RM. Soedarsono, this applies to public school, the Indonesian Air Force, and GeloraBahana Patria Choir. As for character education, the specialty of Yogyakarta reflects its identity as acity of struggle, city of education and city of arts and culture. According to the theory of transformation,something new, including the arrangements of patriotic songs in the forms of march, hymn, romancefor parade, military defile and aubade, is to restore the spirit of nationalism and patriotism. The successof transforming the patriotic songs so as to have new atmosphere is dependent on the various abilitiesto make the arrangement works, so that they can draw attention from the doers and the listeners andfunction in ceremony and performance art. In line with the Decree of the Ministry of National Educationof 2011 items 10 and 11 regarding the values of nationalism and patriotism, we can realize those valuesby singing patriotic songs, using Indonesian language as the unifying language, and acknowledging,appreciating and commemorating the services of national heroes.